Identifying recreational physical activities associated with muscle quality in men and women aged 50 years and over. Issue 3 (16th April 2014) - Barbat-Artigas, Sébastien; Dupontgand, Sophie; Pion, Charlotte H.; Feiter-Murphy, Yannick; Aubertin-Leheudre, Mylène
Abstract : Background: Several studies conducted in a laboratory‐related environment have shown that exercise is associated with increased muscle quality in older adults. The aim of the present study was to investigate whether recreational exercise may also be associated with muscle quality in men and women aged 50 years and over. Methods: Data are from 312 individuals (215 women) aged 50 years and older. Body composition (dual‐energy X‐ray absorptiometry) and knee extension strength (KES) of the right leg (one repetition maximum) were assessed. Muscle quality (MQ) (KES/right lower limb lean mass) was calculated. Recreational exercises (duration and weekly amount) were determined by structured interview. Results: The duration of the period during which participants practiced resistance activities was the only predictor of MQ ( p = 0.018) and explained an additional 1.6 % of the variance in MQ, after controlling for age and gender. Furthermore, the weekly amount of practice of aerobic activities significantly interacted with age ( p < 0.001) to determine MQ. Conclusions: Findings suggest that long‐term engagement in resistance exercise is beneficial for muscle quality and should be encouraged. Furthermore, beyond 60 years, aerobic activities also seem to be positively associated with muscle quality.